Ambient air quality measurements from a continuously moving mobile platform: Estimation of area-wide, fuel-based, mobile source emission factors using absolute principal component scores. (March 2017) - Larson, Timothy; Gould, Timothy; Riley, Erin A.; Austin, Elena; Fintzi, Jonathan; Sheppard, Lianne; Yost, Michael; Simpson, Christopher
Abstract: We have applied the absolute principal component scores (APCS) receptor model to on-road, background-adjusted measurements of NOx, CO, CO2, black carbon (BC), and particle number (PN) obtained from a continuously moving platform deployed over nine afternoon sampling periods in Seattle, WA. Two Varimax-rotated principal component features described 75% of the overall variance of the observations. A heavy-duty vehicle feature was correlated with black carbon and particle number, whereas a light-duty feature was correlated with CO and CO2 . NOx had moderate correlation with both features. The bootstrapped APCS model predictions were used to estimate area-wide, average fuel-based emission factors and their respective 95% confidence limits. The average emission factors for NOx, CO, BC and PN (14.8, 18.9, 0.40 g/kg, and 4.3 × 10 15 particles/kg for heavy duty vehicles, and 3.2, 22.4, 0.016 g/kg, and 0.19 × 10 15 particles/kg for light-duty vehicles, respectively) are consistent with previous estimates based on remote sensing, vehicle chase studies, and recent dynamometer tests. Information on the spatial distribution of the concentrations contributed by these two vehicle categories relative to background during the sampling period was also obtained. Highlights: Heavy and light duty fuel-based emission factors estimated for NOx, CO, BC, and PN. Factors are consistent with remote sensing, vehicle chase, and dynamometer studies. Method relies solely on observed on-road concentration measurements.